The Role of Exosomes and Exosomal MicroRNA in Cardiovascular Disease - Zheng, Dongdong; Huo, Ming; Li, Bo; Wang, Weitie; Piao, Hulin; Wang, Yong; Zhu, Zhicheng; Li, Dan; Wang, Tiance; Liu, Kexiang (Frontiers in Cell and Developmental Biology, 2021)
Exosomes are small vesicles (30–150 nm in diameter) enclosed by a lipid membrane bilayer, secreted by most cells in the body. They carry various molecules, including proteins, lipids, mRNA, and other RNA species, such as long non-coding RNA, circular RNA, and microRNA (miRNA). MiRNAs are the most numerous cargo molecules in the exosome. They are endogenous non-coding RNA molecules, approximately 19–22-nt-long, and important regulators of protein biosynthesis. Exosomes can be taken up by neighboring or distant cells, where they play a role in post-transcriptional regulation of gene expression by targeting mRNA. Exosomal miRNAs have diverse functions, such as participation in inflammatory reactions, cell migration, proliferation, apoptosis, autophagy, and epithelial–mesenchymal transition. There is increasing evidence that exosomal miRNAs play an important role in cardiovascular health. Exosomal miRNAs are widely involved in the occurrence and development of cardiovascular diseases, such as atherosclerosis, acute coronary syndrome, heart failure, myocardial ischemia reperfusion injury, and pulmonary hypertension. In this review, we present a systematic overview of the research progress into the role of exosomal miRNAs in cardiovascular diseases, and present new ideas for the diagnosis and treatment of cardiovascular diseases.